The use of different 17β-estradiol hormone doses and water temperatures to control cannibalism in catfish Clarias gariepinus seed - Putri, Hylda Khairah; Zairin Jr., Muhammad; Carman, Odang; Diatin, Iis (Jurnal Akuakultur Indonesia, 2020)
Cannibalism is a major problem in the intensive catfish hatchery that caused high mortality. This phenomenon is allegedly due to the high level of testosterone hormones in the early larvae and seed stages. Testosterone is a maternal steroid hormone that is transferred directly by the parent to the egg. Catfish broodstock has high testosterone levels during the gonad maturation phase and it enters the eggs during the process of vitellogenesis. A high level of testosterone is considered to cause catfish seeds to behave aggressively and subsequently encourage cannibalism. This testosterone level may be reduced by estrogen through a negative feedback mechanism. This experiment aimed to evaluate the use of several 17β-estradiol doses at different water temperatures to control cannibalism in catfish seeds. This experiment used two factors, i.e. 17β-estradiol doses (0, 20, and 50 mg/kg) coated in the diet and water temperatures (28 and 31°C). The results showed that 17β-estradiol levels in catfish seeds increased with increasing experimental length. The use of 17β-estradiol at low water temperature (28°C) was better in decreasing mortality, while the dose of 50 mg/kg17β-estradiol which applied at 28°C was the best combination in controlling cannibalism on catfish seeds. Keywords: 17β-estradiol, cannibalism, Clarias gariepinus, seed. ABSTRAK Kanibalisme merupakan salah satu masalah utama dalam pembenihan ikan lele intensif karena menyebabkan kematian yang tinggi. Fenomena ini diduga karena kadar hormon testosteron yang tinggi pada tahap larva dan benih. Testosteron merupakan hormon steroid maternal yang ditransfer secara langsung oleh induk ke telur. Induk ikan lele memiliki kadar testosteron yang tinggi pada fase pematangan gonad dan masuk ke dalam telur selama proses vitelogenesis. Tingginya kadar testosteron diduga menyebabkan benih berperilaku agresif dan akan mendorong kanibalisme. Kadar testosteron dapat ditekan dengan meningkatkan kadar hormon estrogen melalui mekanisme feedback negatif. Penelitian ini bertujuan mengevaluasi penggunaan dosis estradiol-17β dan suhu pemeliharaan yang berbeda untuk mengendalikan kanibalisme pada benih ikan lele. Penelitian ini menggunakan dua faktor yaitu dosis estradiol-17β yang berbeda (0, 20, dan 50 mg/kg) yang diberikan melalui pakan, dan suhu pemeliharaan yang berbeda (28 dan 31°C). Hasil penelitian menunjukkan bahwa konsentrasi estradiol-17β pada benih ikan lele meningkat seiring dengan lamanya pemeliharaan. Penggunaan estradiol-17β pada suhu 28°C lebih baik dalam mengurangi mortalitas, sementara dosis estradiol-17β 50 mg/kg pada suhu pemeliharaan 28°C adalah kombinasi terbaik dalam mengendalikan kanibalisme pada benih ikan lele. Kata kunci: benih, Clarias gariepinus, estradiol-17β, kanibalisme.